On Janowski functions associated with (n, m)-symmetrical functions. Issue 1 (11th December 2019) - Alsarari, Fuad; Latha, Satyanarayana; Bulboacă, Teodor
Abstract: The aim in the present work is to introduce and study new subclasses of analytic functions that are defined by using the generalized classes of Janowski functions combined with the ( n, m ) -symmetrical functions, that generalize many others defined by different authors. We gave a representation theorem for these classes, certain inherently properties, while covering and distortion properties are also pointed out.